The Ivory Poachers - Pfotenhauer, Linda (Reeds Publishing Inc, 1993)
One of a series of readers for African students which aims to help them to develop an awareness and a love of language, and consists of stories from all over Africa. In this story Japala fulfils a dream by becoming a game scout. She also falls in love - but is then captured by ivory poachers.
Keywords: Juvenile literature-Fiction